A professional learning model that cultivates primary science classrooms' representational profiles. (2016) - Nichols, Kim; Gillies, Robyn; Kleiss, Donna
Highlights: A professional learning model that immerses teachers in representational practices: Improves teachers' self-efficacy to teach geology with representations; Fosters teachers' competencies to interpret, explain and choose representations; Promotes students' conceptual and representational competencies; and Cultivates representational profiles despite variation across classes and teachers. Abstract: The aim of the study was to explore representational profiles of seven primary science classrooms prior to and following professional learning around representational practices. Teachers' self-efficacy to teach year six geology with representations and their competencies to interpret, explain and choose geology-based representations significantly improved. Teachers with very different years of teaching experience chose the same types of representations to teach the same concepts. Despite variation between classes and students, there was a significant and substantial improvement in student competencies to interpret, understand and create representations to explain geological concepts and this improvement occurred across all classes. The findings suggest the professional learning promoted conceptual and representational competencies in all classes despite the differences across the teachers and their classrooms.